Legal Analysis of the Validity and Enforcement of Fiduciary Guarantees in Default Disputes Based on Decision Number 243/Pdt.G/2017/PN Smn. - Cyndy, Yessyka Cyndy Utami; Fajrul Mumtaz Kurniawan (Fakultas Hukum Universitas Widya Mataram, 2026)
Abstract This study aims to analyze the validity and execution of fiduciary security with market stall lease rights as collateral in default disputes, based on Decision Number 243/Pdt.G/2017/PN Smn. The background of this research lies in banking practices that frequently use stall lease rights as collateral, despite the fact that, normatively, lease rights are not classified as property rights under the Indonesian secured transactions law. The research method applied is normative legal research with a literature study approach, involving statutory regulations, legal doctrines, jurisprudence, and case analysis. The findings show that, under Indonesian civil law, stall lease rights are not explicitly recognized as fiduciary objects in Law Number 42 of 1999 concerning Fiduciary Security. Nevertheless, in practice, lease rights possess significant economic value and may serve as collateral, provided that the agreement fulfills the validity requirements under Article 1320 of the Civil Code and has obtained permission from the market management authority as the asset owner. The Sleman District Court Decision Number 243/Pdt.G/2017/PN Smn emphasized that although the collateral object is not a classical property right, the court still protected the creditor’s position based on the principle of pacta sunt servanda. The execution of fiduciary security over market stall lease rights must comply with the provisions of the Fiduciary Security Law, particularly after the Constitutional Court Decision Number 18/PUU-XVII/2019, which requires consensus on default or voluntary surrender by the debtor, or otherwise through a court order. The conclusion of this research is that the use of stall lease rights as fiduciary collateral remains possible, but it must adhere to civil law requirements, administrative regulations, and prudential principles to avoid legal disputes. Keywords: fiduciary security, stall lease rights, default, execution, legal certainty